2011
DOI: 10.1139/f2011-078
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of biomass in Norwegian fish farms

Abstract: We have constructed a statistical model to forecast, with uncertainty, the stock of Norwegian farmed Atlantic salmon (Salmo salar). The model provided good predictions of future biomass of Norwegian farmed salmon and can also be used to perform "what-if" analysis exploring the impact of varying scenarios for stocking and slaughtering. The model is based on the number of fish in each mass class (0-1, 1-2, …, 10+ kg) and their average mass. The model, which is related to standard size-structured models, computes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Even though the suggested equation in this study described growth satisfactorily, further efforts should be performed to increase the accuracy of predictions and parametrize an equation that includes the effect of environmental variables. Although growth rates depend on many factors, such as feed, light conditions, oxygen and SST (Løland, Aldrin, Steinbakk, Huseby, & Grøttum, ), evidently temperature has been the most relevant factor to explain PBFT growth rates (Jusup, Klanjscek, Matsuda, & Kooijman, ). Moreover, despite food availability affects the maximum individual size, the size of the ration is affected by SST (Jusup et al., ; Katavić, Tičina, & Franičević, ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the suggested equation in this study described growth satisfactorily, further efforts should be performed to increase the accuracy of predictions and parametrize an equation that includes the effect of environmental variables. Although growth rates depend on many factors, such as feed, light conditions, oxygen and SST (Løland, Aldrin, Steinbakk, Huseby, & Grøttum, ), evidently temperature has been the most relevant factor to explain PBFT growth rates (Jusup, Klanjscek, Matsuda, & Kooijman, ). Moreover, despite food availability affects the maximum individual size, the size of the ration is affected by SST (Jusup et al., ; Katavić, Tičina, & Franičević, ).…”
Section: Discussionmentioning
confidence: 99%
“…The data contain two types of errors; i) farmers fail to report data, and ii) farmers report incorrect numbers (measurement error). The first error is impossible to observe in the dataset but is documented by Løland et al (2011), who have access to the individual farmers' data, while the second error can be observed to some extent. At the beginning and end of the data series for each county when few fish are present in the pens, some strange observations are reported.…”
Section: Procedures and Datamentioning
confidence: 99%
“…To my knowledge, only two other studies have examined the development of biomass on an aggregate level. Asheim et al (2011) study how biomass development affects short run supply using aggregated time series data, while Løland et al (2011) have established a model to predict biomass in Norwegian fish farms using data from individual farmers that they have aggregated to regional data. The latter study computes the number of fish growing into the next weight class (0-1 kg, 1-2 kg, …, 10 kg).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, we found that Løland et al. () model the distribution of the weight of a specific weight class as a beta distribution and estimate the parameters based on real data from a Norwegian fishery. The choice of the beta distribution seems to be arbitrary and only motivated by the tractability that this distribution provides.…”
Section: Freshwater Planning Modelmentioning
confidence: 99%
“…We discussed this assumption with the freshwater planning team and they agreed that this was a reasonable modeling assumption; however, we were not able to validate this empirically. In the literature, we found that Løland et al (2011) model the distribution of the weight of a specific weight class as a beta distribution and estimate the parameters based on real data from a Norwegian fishery. The choice of the beta distribution seems to be arbitrary and only motivated by the tractability that this distribution provides.…”
Section: Planning Support Modelsmentioning
confidence: 99%